Deuterium absorption properties of V85Ni15 and evidence of isotope effect. (26th July 2019) - Brutti, S.; Tosti, S.; Santucci, A.; Paolone, A.
Abstract: The pressure-composition absorption isotherms of deuterium in an alloy with nominal composition V85 Ni15 were measured between 87 and 400 °C for pressures up to ≈17 bar. For T ≤ 144 °C one observes the occurrence of a solid solution α phase for D/M < 0.15, the coexistence of α and β phase up to D/M ≈ 0.5 and a subsequent change to a different phase for higher deuterium concentrations. For temperatures higher than 200 °C only a solid solution with a deuteration enthalpy ΔHdeutr  = 47 ± 2 kJ/mol is detected. The critical temperature of this V-Ni alloy (144 °C ≤ T*≤200 °C) is much higher than that of pure V (100 °C). Moreover, well above the critical temperature, one can observe a "normal" isotope effect, i.e. the equilibrium pressure of the V85 Ni15 -H system is higher than that of V85 Ni15 -D. Highlights: Deuterium absorption in V85 Ni15 . Occurrence of α and β phase below 144 °C. Only a α phase above 200 °C (ΔHdeutr  = 47 ± 2 kJ/mol). Normal isotope effect (the equilibrium pressure in V85 Ni15 -H system is higher than in V85 Ni15 -D).